Importance of the Static Infrastructure for Dissemination of Information within Intelligent Transportation Systems - Jiří Jelínek; Jiří Čejka; Josef Šedivý (Communications - Scientific letters of the University of Zilina, 2022)
Intelligent transportation systems (ITS) are a today´s hot topic, especially in the context of the development of information technologies, which can be employed in transportation. Although the scope and the technical solution of these systems may vary, they are frequently based on VANET (Vehicular ad hoc network), i.e. a communication network, which is primarily generated among the moving subjects, which form ITS. Given the highly dynamic VANET, the questions are raised as to the data transmission. This paper is aimed to make a detail analysis of the communications within VANET using the simulation model, which includes the static infrastructure of ITS and to experimentally verify the impact of this infrastructure on the dynamics of information spreading in ITS. The authors present the results obtained from a few different scenarios, which have been tested.